Non-Conformist Conscience? Individual Conscience and the Authority of the Church from John Calvin to the Present* - Bradbury, John P. (Ecclesiology, 2014)
This article traces the continuities and discontinuities in the idea of individual conscience and its relationship to ecclesial authority from the Reformation period to the present day. It does this with particular reference to the Reformed theological tradition, particularly the British non-conformist traditions that today form the United Reformed Church. Through an engagement with John Calvin, William Ames, confessional texts and later thinkers, key shifts in the understanding of conscience, from being informed by revelation within the context of the Church, to the more contemporary individual subjective model are explored. An account of the place of conscience within the union negotiations that brought the URC into existence is offered based on archival material. It is argued that the shift of understandings of freedom of conscience to the secular political realm, opens up a specifically ecclesiological space in which the relationship between individual conscience and ecclesial authority has been, and can be, reconceived.